Species and Genetic Diversity of Representatives of the Anaplasmataceae Family Found in the Sympatry Zone of the Ixodes, Dermacentor and Haemaphysalis Genera Ticks - E. K. Doroshchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Introduction.On the territory of the Ekhirit-Bulagatsky district of the Irkutsk region zones of sympatry of four Ixodes ticks species are found, where the species and genetic diversity of infectious agents transmitted through tick bites may be more pronounced than in foci with a mono-dominant type of ticks’ population. In this connection, the study of the species and genetic diversity of representatives of the Anaplasmataceae family in the sympatry zone of the Ixodes ticks of closely related species was of scientific interest.Objective: To study the species and genetic diversity of members of the Anaplasmataceae family in the zones of sympatry of Ixodes ticks Ixodes persulcatus, Dermacentor silvarum, D. nuttalli and Haemaphysalis concinna, to identify the main carriers and potential reservoir hosts of ehrlichia and anaplasma.Methods. In the course of the study, 1106 specimens of adult ticks and 49 samples of small mammalian livers from the Ekhirit-Bulagatsky area were analyzed. Anaplasma and ehrlichia DNA were detected by two-round PCR in the presence of genus- and species-specific primers from the 16S rRNA gene region. The nucleotide sequences of the 16S rRNA gene and the fragment of the groESL operon were identified in some samples. Sequencing was carried out according to the Sanger method. Comparative analysis was performed using the BLASTN program and ClustalW method. Epidemiological data analysis was performed using parametric methods of statistical processing of the material.Results. The DNA of Ehrlichia muris and Anaplasma phagocytophilum were detected in all studied species of ticks in their sympatry area. However, the rate of infection of taiga ticks was significantly higher than that of H. concinna and Dermacentor spp. Potential reservoir hosts of the Anaplasmataceae family members can be classified as Microtus oeconomus, M. gregalis, Myodes rutilus and Sorex spp. When analyzing the nucleotide sequences of the 16S rRNA gene, three genetic variants of anaplasma were detected. The nucleotide sequences of the A. phagocytophilum groESL operon belonged to two genetic groups.